Correction: Influenza vaccination hesitancy in five countries of South America. Confidence, complacency and convenience as determinants of immunization rates. - Miguel Ángel González-Block; Emilio Gutiérrez-Calderón; Blanca Estela Pelcastre-Villafuerte; Juan Arroyo-Laguna; Yamila Comes; Pedro Crocco; Andréa Fachel-Leal; Laura Noboa; Daniela Riva-Knauth; Berenice Rodríguez-Zea; Mónica Ruoti; Elsa Sarti; et al. (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0243833.].